Relevance of Angiographic Patterns in Patients with Chronic Kidney Disease and Its Therapeutic Implications in Chronic Limb-threatening Ischemia - Sumanshi Singh; Sapna Vishnurajesh Tiwari; Raghuram Sekhar; Sharad Sheth (Indian Journal of Vascular and Endovascular Surgery)
Background: The concept of “renal foot” which has been attributed to the characteristic involvement of posterior tibial artery (PTA) and lateral plantar artery in chronic limb-threatening ischemia (CLTI) patients with end-stage renal disease as comorbidity. (Image of renal foot) Aims and Objectives: This concept was examined further along with its possible therapeutic implications. Materials and Methods: Retro-prospective, observational, single institute study carried out over 2 years in 50 chronic kidney disease (CKD) and 50 non-CKD patients who suffered from CLTI warranting an endovascular intervention. Results: PTA involvement was the highest in the whole study population, however, with no significant difference between the CKD and non-CKD groups. The highest number of the study group had class 4 Graziani classification and the highest number of CKD patients had class 3 Graziani reinforcing the extensive peripheral infrapopliteal involvement in CLTI. Conclusion: CLTI in CKD patients, though associated with more severe peripheral arterial disease, does not affect isolated vessels disproportionately. The overall morbidity and mortality were higher in the CKD group due to overall poorer health, with good healing of wounds in the rest of the population. Endovascular revascularization was effective regardless of vessel involvement or CKD status, thereby negating its therapeutic implications.